Effect of intravenous dexamethasone on the anaesthetic characteristics of peripheral nerve block: a double-blind, randomised controlled, dose–response volunteer study. (January 2020) - Short, Anthony; El-Boghdadly, Kariem; Clarke, Hance; Komaba, Tomomi; Jin, Rongyu; Chin, Ki Jinn; Chan, Vincent
Abstract: Background: Intravenous dexamethasone is thought to prolong the duration of peripheral nerve block, but the dose–response relationship remains unclear. The aim of this volunteer study was to evaluate the dose–response effect of i.v. dexamethasone on the prolongation of median nerve block. Methods: In a double-blind, randomised controlled study, 18 volunteer subjects received two median nerve blocks separated by a washout period. One block was conducted alongside an infusion of saline and the other alongside i.v. dexamethasone 2, 4, or 8 mg. The primary outcome was time to return of normal pinprick sensation. Secondary outcomes included thermal quantitative sensory testing (QST) for the time to return of cold detection threshold (CDT), warm detection threshold (WDT), cold pain threshold (CPT), heat pain threshold (HPT), area under QST curves, grip strength, and the incidence of adverse effects. Results: The primary outcome, time to recovery of pinprick sensation, was similar between volunteers receiving saline or i.v. dexamethasone, regardless of dose ( P =0.99). The time to recovery of QST milestones was similar between groups, although area under QST curves indicated prolongation of CDT (0 vs 8 mg, P =0.002) and WDT (0 vs 2 mg, P =0.008; 0 vs 4 mg, P =0.001; 0 vs 8 mg, P <0.001). There was no difference in motor recovery or adverse effects. Conclusions: Intravenous dexamethasone failed to significantly prolong the duration of pinprick anaesthesia regardless of dose. However, area under QST curve analysis indicated a dose-independent prolongation of CDT and WDT, the clinical significance of which is unclear. Clinical trial registration: NCT02864602 (clinicaltrials.gov ).